Where to Locate? The Correlation Between Spatial Proximity and Location Choice of New Firms: The Case of Pakistan*. Issue 2 (7th July 2021) - Haroon, Maryiam; Chaudhry, Azam
Abstract : The formation of new firms is an important determinant of regional economic development and agglomeration is a key factor affecting the formation and scale of operations of new firms. The present paper is among the first to explore the relationship between agglomeration economies (using localization and urbanization economies) and new firms' formation and scale of operations in a developing country. We make use of rich firm‐level data and find that agglomeration has a significant impact on the formation of new firms and their scale of operation in Punjab, Pakistan. Our findings also reveal that localization at all scales (small, medium and large) has a positive correlation with the arrival of new firms, while medium‐scale and large‐scale localization is positively correlated with the scale of operation of new firms.